Does acute peripheral trauma contribute to idiopathic adult-onset dystonia?. (February 2020) - ,; Ferrazzano, Gina; Lalli, Stefania; Silvestre, Francesco; Manganelli, Fiore; Di Biasio, Francesca; Marchese, Roberta; Demonte, Giulio; Santangelo, Domenico; Devigili, Grazia; Durastanti, Valentina; Turla, Marinella; et al.
Abstract: Background: Acute peripheral trauma is a controversial risk factor for idiopathic dystonia. Materials and methods: We retrospectively analyzed data from the Italian Dystonia Registry regarding the occurrence of acute peripheral trauma severe enough to require medical attention in 1382 patients with adult-onset idiopathic dystonia and 200 patients with acquired adult-onset dystonia. Results: Patients with idiopathic and acquired dystonia showed a similar burden of peripheral trauma in terms of the number of patients who experienced trauma (115/1382 vs. 12/200, p = 0.3) and the overall number of injuries (145 for the 1382 idiopathic patients and 14 for the 200 patients with secondary dystonia, p = 0.2). Most traumas occurred before the onset of idiopathic or secondary dystonia but only a minority of such injuries (14 in the idiopathic group, 2 in the acquired group, p = 0.6) affected the same body part as that affected by dystonia. In the idiopathic group, the elapsed time between trauma and dystonia onset was 8.1 ± 9.2 years; only six of the 145 traumas (4.1%) experienced by 5/1382 idiopathic patients (0.36%) occurred one year or less before dystonia onset; in the acquired dystonia group, the two patients experienced prior trauma to the dystonic body part 5 and 6 years before dystonia development. Discussion and conclusion: Our data suggest that the contribution of peripheral acute trauma to idiopathic dystonia is negligible, if anything, and likely involves only a small subset of patients. Highlights: Acute peripheral trauma is a controversial risk factor for idiopathic dystonia. The role of trauma in idiopathic dystonia has relevant implications. The contribution of peripheral acute trauma to idiopathic dystonia is negligible.